Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21276/ap.2017.6.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular secretion of lignocellulolytic enzymes by diversewhite rot asidiomycetes fungi

Abstract: Rich source of biota includes several white rot fungi, were reported in Western Ghats regions of Tamil Nadu, India. The effective identification of white rot fungi and their lignocellulolytic enzymes play a crucial role for degradation of agricultural and industrial wastes to maintain su sta ina ble ecosystem. T hus, the present study was conducted to assess the secretion of lignocellulolytic enzymes of diverse white rot fungi, collected from Western Ghats regions of Tamil Nadu, comprising of Kotagiri and Ooty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
1
1
2
Order By: Relevance
“…The enzyme cocktail that was obtained after 4 days of fungal growth on hay as a carbon source, in subsequent hay hydrolysis demonstrated 63% conversion rate into reducing sugars. These observations to some extent contradict with other studies where white-rot fungi produced the most active enzymes after 12 days of incubation [ 21 ]. The differences could be explained by previous assessment of only individual enzymes or their limited combinations [ 8 , 21 ] or the by more intense binding of the enzyme to carbohydrate source (hay) at later incubation stage and inefficient recovery of that enzyme fraction.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The enzyme cocktail that was obtained after 4 days of fungal growth on hay as a carbon source, in subsequent hay hydrolysis demonstrated 63% conversion rate into reducing sugars. These observations to some extent contradict with other studies where white-rot fungi produced the most active enzymes after 12 days of incubation [ 21 ]. The differences could be explained by previous assessment of only individual enzymes or their limited combinations [ 8 , 21 ] or the by more intense binding of the enzyme to carbohydrate source (hay) at later incubation stage and inefficient recovery of that enzyme fraction.…”
Section: Resultscontrasting
confidence: 99%
“…These observations to some extent contradict with other studies where white-rot fungi produced the most active enzymes after 12 days of incubation [ 21 ]. The differences could be explained by previous assessment of only individual enzymes or their limited combinations [ 8 , 21 ] or the by more intense binding of the enzyme to carbohydrate source (hay) at later incubation stage and inefficient recovery of that enzyme fraction. In this study, the performance of the whole crude enzyme cocktail without purification and removal of any specific protein fraction was assessed.…”
Section: Resultscontrasting
confidence: 99%
“…Our results coincide with reports of compounds derived from agro-industrial residues, such as wheat straw, rice straw, corn stubble, and cane bagasse, functioning as inducers of the main lignin-modifying enzymes in white rot fungi [64][65][66]. Furthermore, the addition of dyes had a clear induction effect on enzymatic activity [67,68].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the findings presented here, they did not observe the significant influence of glucose or glycerol on laccase production. Various reports have indicated that the production of LMEs in basidiomycetes is dependent on the carbon and nitrogen sources used, as well as the presence of aromatic compounds in the culture medium ( Elisashvili, Kachlishvili & Asatiani, 2018 ; Stajić et al, 2006 ; Thiribhuvanamala et al, 2017 ). For instance, Elisashvili et al (2002) demonstrated the effect of different carbon sources and aromatic compounds on the lignocellulolytic enzyme activity of different edible and medicinal basidiomycetes, concluding that it is possible not only to increase lignocellulolytic activity substantially, but also to trigger their preferential synthesis by supplementing the culture medium with nutritional compounds.…”
Section: Discussionmentioning
confidence: 99%